Perception of the use of LMS/ i-Learn portal and Telegram / Aeimi Ruzanna Abu Hassim, Abdul Fattah Abd. Gani, Eliyas S. Mohandas - Abu Hassim, Aeimi Ruzanna; Abd. Gani, Abdul Fattah; Mohandas, Eliyas S. (UiTM Press, 2017)
The purpose of this study is to identify the perception of Universiti Teknologi MARA (UiTM) students regarding the use of the Telegram mobile application and the UiTM Learning Management System (LMS) known as the i-Learn Portal for the purpose of discussion and dissemination of audio files for the Listen-Interact-Reflect-Act/Answer (LIRA) assignment tasked for the sample group. It is also served as reminders for assignments, quizzes and tests due dates. In terms of connection and mobility, most of these students have difficulty in accessing and communicating using the webpage, hence not being able to utilise it to its fullest. Telegram is seen as more convenient as the interface is much like other mobile instant messaging systems that facilitate students in responding to their lecturer and to communicate with their peers at any time. The study conducted on the students who took Integrated Language Skills: Listening (ELC120) course found that students preferred to use Telegram compared to the i-Learn Portal. They were found to express their emotions (using emoticons) more freely and could responded better to questions in Telegram.